2015
DOI: 10.1159/000381558
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Bilateral Subthalamic Nucleus Deep Brain Stimulation on Impulsivity and Prepulse Inhibition in Parkinson's Disease Patients

Abstract: Background: At least 14% of Parkinson disease (PD) patients develop impulse control disorders (ICDs). The pathophysiology behind these behaviors and the impact of deep brain stimulation in a real-life setting remain unclear. Objectives: We prospectively examined the impact of bilateral subthalamic nucleus deep brain stimulation (STN-DBS) on ICDs in PD patients, as well as the relationship between impaired sensorimotor gaiting and impulsivity. Methods: Patients undergoing bilateral STN-DBS were assessed for ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
3
25
0
Order By: Relevance
“…We found 12 studies investigating the prevalence of ICDs (gambling, compulsive shopping, binge eating, hypersexuality, punding, DDS) in a total of 582 PD patients pre-and (6-12 months) post STN DBS (Ardouin et al, 1999;Lim et al, 2009;Lhommée et al, 2012;Shotbolt et al, 2012;Eusebio et al, 2013;Kim et al, 2013;Amami et al, 2015;Castrioto et al, 2015;Gee et al, 2015;Merola et al, 2017). The combined prevalence of ICDs in these patients was 28% (N = 162) before STN DBS and 6% (N = 32) after STN DBS (with variable post-surgical LEDD decreases).…”
Section: Impulse Control Disordersmentioning
confidence: 99%
“…We found 12 studies investigating the prevalence of ICDs (gambling, compulsive shopping, binge eating, hypersexuality, punding, DDS) in a total of 582 PD patients pre-and (6-12 months) post STN DBS (Ardouin et al, 1999;Lim et al, 2009;Lhommée et al, 2012;Shotbolt et al, 2012;Eusebio et al, 2013;Kim et al, 2013;Amami et al, 2015;Castrioto et al, 2015;Gee et al, 2015;Merola et al, 2017). The combined prevalence of ICDs in these patients was 28% (N = 162) before STN DBS and 6% (N = 32) after STN DBS (with variable post-surgical LEDD decreases).…”
Section: Impulse Control Disordersmentioning
confidence: 99%
“…These observations suggest that modulation of STN with DBS, although it improves motor functions, may tend in parallel to favor the appearance of certain impulsive behaviors by acting on mechanisms involved in response initiation and/or selection . However, to date, the impact of DBS (and its interaction with dopamine agonist reduction) on the development of ICD is unclear and still quite controversial, given that studies using different approaches have shown conflicting results …”
Section: Behavioral and Affective Complications In Pdmentioning
confidence: 99%
“…91 However, to date, the impact of DBS (and its interaction with dopamine agonist reduction) on the development of ICD is unclear and still quite controversial, given that studies using different approaches have shown conflicting results. [93][94][95] Fatigue is a common nonmotor symptom in PD. Recent studies have reported that PD patients with higher level of fatigue may show anticorrelated metabolic changes in cortical regions associated with the salience (i.e., right insular region) and default (i.e., bilateral posterior cingulate cortex) networks.…”
Section: Behavioral and Affective Complications In Pd What Molecular mentioning
confidence: 99%
“…However, change in ICD status post-STN DBS has been at best inconsistent across reported studies (Santangelo et al ., 2013). In two large studies, ICDs have been shown to worsen after DBS (Gee et al ., 2015). In others, STN DBS has been associated with improvement in, (Gee et al ., 2015) and resolution of, pre-existing ICDs, even in studies that control for dopaminergic medications (Demetriades et al ., 2011) (Ardouin et al ., 2006).…”
Section: Impulse Control Parkinson’s Disease and The Stn: Major mentioning
confidence: 99%